Study Ethnomedicine Betimun: The Traditional Steam Bath Herb of Saibatin Sub-tribe, Lampung - Wakhidah, Anisatu Z; Silalahi, Marina (STRADA : Jurnal Ilmiah Kesehatan, 2020)
The study revealed as many as 6 species from 3 families used in the preparation of betimun herb, Zingiberaceae was the family with the highest number of species (4 species). The used part of all plant species was leaves, while the acquisition source was from homegarden. The betimun herb was made by boiling the plants leaves. The usage way by confining the user with a sarong then the herb placed between his/her legs. Biological activities contained in the secondary metabolite compound composition of betimun herb were anti-fungal, anti-bacterial, antioxidant, aromatherapy, anti-oxidant, anti-glycation, sedative, anti-hypertensive, and astringent. This study proved that the betimun concoction has roles in eliminating body odor, fatigue, and aches; preventing and treating vaginal discharge; recovering the postpartum women's condition; slowing down the aging process, and accelerating the metabolic process. Betimun concoction potentially to be developed as a ready-use product such as phyto-simplicia.